2021
DOI: 10.1177/10664807211023875
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience during COVID-19 Pandemic: A Literature Review

Abstract: Introduction: The COVID-19 pandemic has spread rapidly in many countries. This pandemic has led to short-term as well as long-term psychosocial and mental health implications for all family members. The magnitude of family resilience is determined by many vulnerability factors like developmental age, educational status, preexisting mental health condition, being economically underprivileged or being quarantined due to infection or fear of infection. Methods: PubMed, SCOPUS, MEDLINE, Google Scholar, Cochrane, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 22 publications
(37 reference statements)
6
70
0
3
Order By: Relevance
“…Coinciding with re-openings for in person visiting in rounds 2 and 3 in many provinces, connecting with friends and family virtually via phone and video chat was less frequently reported in round 2 (31.7%) and round 3 (37.9%) compared with round 1 (50.5%), whereas connecting in person with friends and family in "my bubble" and enjoying outdoor activities with friends and family were more frequently reported in round 2 (29.6% and 36.4%, respectively) and round 3 (24.8% and 30.6%, respectively). Other research has similarly identified the maintenance of family routines, adaptability, and family cohesion as factors of family resilience during the pandemic [30]. Children's perceived connectedness to caregivers has also been found to predict better mental health outcomes for children during the pandemic [38].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Coinciding with re-openings for in person visiting in rounds 2 and 3 in many provinces, connecting with friends and family virtually via phone and video chat was less frequently reported in round 2 (31.7%) and round 3 (37.9%) compared with round 1 (50.5%), whereas connecting in person with friends and family in "my bubble" and enjoying outdoor activities with friends and family were more frequently reported in round 2 (29.6% and 36.4%, respectively) and round 3 (24.8% and 30.6%, respectively). Other research has similarly identified the maintenance of family routines, adaptability, and family cohesion as factors of family resilience during the pandemic [30]. Children's perceived connectedness to caregivers has also been found to predict better mental health outcomes for children during the pandemic [38].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, maintaining a structured, predictable home environment by adhering to family routines appears to mitigate the adverse effects of the pandemic on children's mental health [29]. Maintaining good communication, engaging in shared activities, seeking social support, and practicing gratitude have also been identified as factors helping families cope with stress during the pandemic [30].…”
Section: Impact Of the Pandemic On Parent-child Interactionsmentioning
confidence: 99%
“…Strategies used by diarists to manage the immediate effects of the pandemic are also reflective of coping methods observed in other crisis contexts. Existing research, for example, has observed the role of social contact with others and supportive networks as well as the importance of maintaining regular habits and routines 32,35,36 . Similarly, diarists' strategies demonstrated the ways in which individuals drew on strengths to cope with the unfolding situation.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research, for example, has observed the role of social contact with others and supportive networks as well as the importance of maintaining regular habits and routines. 32 , 35 , 36 Similarly, diarists' strategies demonstrated the ways in which individuals drew on strengths to cope with the unfolding situation. This reflects findings from Rodrigues and colleagues' recent review of social isolation among older adults during the pandemic, which showed individuals finding positivity in daily life, drawing on faith, learning new skills and adapting to online technology to maintain social relationships.…”
Section: Discussionmentioning
confidence: 99%
“…To doświadczenie podzielane przez mieszkańców wszystkich badanych krajów. Generalnie jednak dominującym odczuciem jest większe osamotnienie (Gayatri and Irawaty, 2021).…”
Section: Pandemia I Edukacjaunclassified